The stability of the Doctrinaire inference of Ahl Asunna wal Jama’ah - An Applied Fundamental Study - Alasmari, Halimah Fayiz; Almayouf, Latifah Abdulaziz; Almeshaal, Tahani AbdelAziz (Journal of Islamic Sciences, 2025)
This study examines the concept of consistency (Itrād) as presented in the works of Islamic theology, considering it a fundamental criterion for the validity, coherence, and methodological integrity of reasoning. The refutation of an argument signifies its invalidity, whereas consistency is regarded as an indicator of its soundness. The research aims to demonstrate the methodological consistency of Ahl al-Sunnah wa al-Jamāʿah in both theoretical and applied contexts, highlighting the soundness of their approach, the rigor of their methodology, and their doctrinal steadfastness.The study draws upon evidence from the Prophetic Sunnah and employs an inductive-deductive methodology. It seeks to underscore the manifestations of consistency (Itrād) through selected texts and illustrative examples from the writings of Ahl al-Sunnah wa al-Jamāʿah scholars across the centuries.Among the key findings is the demonstrated consistency of Ahl al-Sunnah in employing solitary reports (Khabar al-Āḥād) in theological matters—such as the beatific vision, divine names, and attributes—while maintaining a strict commitment to avoiding the use of weak hadiths in establishing doctrinal foundations or legal rulings. This methodological stance represents one of the most distinctive features that set their approach apart from opposing theological schools.
Keywords: Approach; Sunnis and Jama'a; Contradictory; Inference